Incorporating shariah compliance, shariah awareness and perceived risk on contributor’s satisfaction behaviour in shariah retirement scheme - Noor Hanny, Samsu Anuar (2022)
Retirement planning is essential for wealth management in preparing for the retirement phase. Modern Portfolio Theory (MPT) focuses on the correlation between risk and investment, which indirectly encourages investors to engage in financial literacy. These fundamentals are important as retirement planning and investment have a mutual relationship. Thus, investors would be able to experience reactions such as satisfaction behaviour. The product offered by EPF is Shariah-compliant and fits with the context of this study. This study aims to understand the contributors’ satisfaction behaviour on retirement planning when only the Shariah-compliant retirement scheme is applied in wealth management. Shariah-compliant retirement schemes have experienced growth over the years. However, there are unclear factors in determining the level of satisfaction of contributors with Shariah-compliant retirement schemes. This study incorporates Shariah compliance, Shariah awareness, and perceived risk as the independent factors in determining the satisfaction behaviour among the contributors. The study adopted the survey approach, using simple random sampling. Survey questionnaires were distributed among the contributors in the selected areas, namely Kuala Lumpur and Penang. Imperatively, the data was tested by Cronbach Alpha and EFA to improve the reliability of the survey. SPSS and Multiple Linear Regression analysis aided this study throughout analyzing the overall data to gain meaningful results. The research findings indicated Shariah compliance, Shariah awareness, and perceived risk positively correlate with contributors’ satisfaction. The study proved that perceived risk highly influences the satisfaction behaviour among the contributors of Shariah retirement schemes. This study could be revamped through future research by exploring on target respondents among rural population as well as including PRS contributors because this expansion would increase the schemes awareness and public association around Malaysia.